2014
DOI: 10.3389/fnhum.2013.00921
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the resting state functional connectivity in the human language system using near infrared spectroscopy

Abstract: We have evaluated the use of phase synchronization to identify resting state functional connectivity (RSFC) in the language system in infants using functional near infrared spectroscopy (fNIRS). We used joint probability distribution of phase between fNIRS channels with a seed channel in the language area to estimate phase relations and to identify the language system network. Our results indicate the feasibility of this method in identifying the language system. The connectivity maps are consistent with anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Using NIRS, Bortfeld, Fava, and Boas (2009) have shown greater hemodynamic activation in left temporal regions to an audio-visual presentation as opposed to visual only in 21 infants aged 6-9 months. Molavi et al (2013) found a left-lateralised response to language in 19 newborn infants, and Peña et al (2003) observed greater activation in left temporal areas in 12 newborns, 2-5 days post-birth, when exposed to normal speech compared to backward speech or silence, suggesting a lateralised response is already present at birth. FMRI data generally support these observations, showing that in 2-day-old newborns, language activation to speech is less lateralised compared to adults (Perani et al, 2011), but a left hemisphere advantage to speech over music is found in slightly older infants (Dehaene-Lambertz et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Using NIRS, Bortfeld, Fava, and Boas (2009) have shown greater hemodynamic activation in left temporal regions to an audio-visual presentation as opposed to visual only in 21 infants aged 6-9 months. Molavi et al (2013) found a left-lateralised response to language in 19 newborn infants, and Peña et al (2003) observed greater activation in left temporal areas in 12 newborns, 2-5 days post-birth, when exposed to normal speech compared to backward speech or silence, suggesting a lateralised response is already present at birth. FMRI data generally support these observations, showing that in 2-day-old newborns, language activation to speech is less lateralised compared to adults (Perani et al, 2011), but a left hemisphere advantage to speech over music is found in slightly older infants (Dehaene-Lambertz et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…[34][35][36][37] Brain mapping with fcMRI and fcNIRS has shown good spatial correlations, 38,39 and good test-retest reliability has been reported with fcNIRS. 40 The higher temporal resolution of NIRS (∼1 ms) as compared to fMRI (seconds) 41 may prevent confounding of physiological noise, such as respiratory and cardiovascular activity, with intrinsic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that frontal and temporal regions of the language network appear anatomically connected already in the first postnatal weeks (41)(42)(43). Moreover, these regions show time-lagged cross-correlations in response to passive listening to speech stimuli (44) and exhibit phase synchronization particularly in the left hemisphere (45). Our study aimed to provide a characterization of the spatiotemporal dynamics within this network during memory assessments by exploring the different configurations as a function of the familiarity of a given speech stimulus-namely, when the system processes a word that is familiar to the newborn versus a totally novel word.…”
Section: Significancementioning
confidence: 99%